Accuracy of virtual planned surgery versus conventional free-hand surgery for reconstruction of the mandible with osteocutaneous free flaps. Issue 9 (September 2020) - Pucci, R.; Weyh, A.; Smotherman, C.; Valentini, V.; Bunnell, A.; Fernandes, R.
Abstract: Virtual surgical planning (VSP) promises higher accuracy, efficiency, and superior patient outcomes, helping normalize outcomes from surgeons of different experience levels. A systematic review was conducted in agreement with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The objective was to evaluate the accuracy and secondarily efficiency of VSP compared with free-hand surgery, for mandibular reconstruction with free flaps. Six studies met inclusion criteria and had quantitative data suitable for meta-analysis. Intercondylar distance and gonion angle were used to assess accuracy, evaluated by mean change from preoperative VSP and postoperative imaging. The mean weighted difference in VSP intercondylar distance was 2.0 mm, compared with 3.9 mm for free hand ( P = 0.101) and mean change in gonion angle for VSP was 3.6°, compared with 7.7° for free hand ( P < 0.05). Efficiency assessed by mean ischemia time, was 73.8 min and 109.9 min, for VSP and free hand, respectively ( P = 0.203), and by total operative time, which was 391.8 min and 457.6 min in the VSP and free hand, respectively ( P = 0.340). VSP is consistently proven to be more accurate and efficient than traditional free-hand surgery; however, a standardized method for accuracy and efficiency measurements is still missing, causing heterogeneity among the scientific reports.